The Effects of the Medicaid Expansion on Hospital Utilization, Employment, and Capital. (April 2023) - Meille, Giacomo; Post, Brady
In recent years, hospitals reacted to changes in demand caused by the Affordable Care Act Medicaid expansions. We conducted a difference-in-differences analysis that compared changes to hospital demand and supply in Medicaid expansion and nonexpansion states. We used 2010–2016 data from the American Hospital Association and the Healthcare Cost Report Information System to quantify changes to hospital utilization and characterize how hospitals adjusted labor and capital inputs. During the period studied, the Medicaid expansion was associated with increases in emergency department visits and other outpatient hospital visits. We find strong evidence that hospitals met increases in demand by hiring nursing staff and weaker evidence that they increased hiring of technicians and investments in equipment. We found no evidence that hospitals adjusted hiring of physicians, support staff, or investments in other capital inputs.